Hubungan Persepsi dan Partisipasi Masyarakat Dalam Pengelolaan Sumberdaya Perikanan Tangkap Berbasis Kearifan Lokal - Topan Christo Bekti; Edy H.P Melmambessy; Sendy L. Merly (Universitas Musamus, Merauke, Papua, 2019)
The purpose of this research are to find out the perception and participation of community towards onthe local wisdom-based capture fisheries resource management and to find out the correlationbetween the perception and participation of Kaiburse villagers on the local wisdom-based capturefisheries resource management. The method of this research is a descriptive by analyzing thecorrelation of the data. The perception of Kaiburse villagers on local policy is very good as shown bythe values: 87.5% of know very well and 12.5% of know about the local wisdom. The participation ofKaiburse villagers towards local wisdom is high which is shown by the value: 42.5% of very often,35% of often and 22.5% of quite often, according to their participation on capture fisheriesmanagement based on local policy is quite high with the value 0.705476, which means that 70.54% ofpeople in Kaiburse village do not only have the local wisdom perception but also participate inmaintaining and implementing local wisdom consistenly. Meanwhile, 29,46% of Kaiburse villagersdid not mean to not participate,but they just unconsistently implementl the local wisdom